2022
DOI: 10.3389/fendo.2022.867940
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Stellate Cell-Immune Interactions in NASH

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the dominant cause of liver disease worldwide. Nonalcoholic steatohepatitis (NASH), a more aggressive presentation of NAFLD, is characterized by severe hepatocellular injury, inflammation, and fibrosis. Chronic inflammation and heightened immune cell activity have emerged as hallmark features of NASH and key drivers of fibrosis through the activation of hepatic stellate cells (HSCs). Recent advances in our understanding of the molecular and cellular pathways in NASH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 155 publications
1
24
0
Order By: Relevance
“… 10 Activated hepatic stellate cells secrete a wide range of proinflammatory cytokines, such as CCL2, CCL5, IL8, chemokine (C-X-C motif) ligand-12 (CXCL12), and express adhesion molecules, such as intercellular adhesion molecule 1 and vascular cell adhesion molecule 1 and chemokine receptors (CCR5), resulting in increased recruitment and infiltration of immune cells into the liver. 34
Figure 1 Pathways of hepatic stellate cell activation and survival during NAFLD. Various factors, such as lipid mediators, free cholesterol accumulation, oxLDL, palmitic acid, LPS, and immune cell–derived profibrotic molecules and growth factors, promote hepatic stellate cell activation and survival during NAFLD.
…”
Section: Role Of Hepatic Stellate Cells In Nonalcoholic Fatty Liver D...mentioning
confidence: 99%
“… 10 Activated hepatic stellate cells secrete a wide range of proinflammatory cytokines, such as CCL2, CCL5, IL8, chemokine (C-X-C motif) ligand-12 (CXCL12), and express adhesion molecules, such as intercellular adhesion molecule 1 and vascular cell adhesion molecule 1 and chemokine receptors (CCR5), resulting in increased recruitment and infiltration of immune cells into the liver. 34
Figure 1 Pathways of hepatic stellate cell activation and survival during NAFLD. Various factors, such as lipid mediators, free cholesterol accumulation, oxLDL, palmitic acid, LPS, and immune cell–derived profibrotic molecules and growth factors, promote hepatic stellate cell activation and survival during NAFLD.
…”
Section: Role Of Hepatic Stellate Cells In Nonalcoholic Fatty Liver D...mentioning
confidence: 99%
“…The factors initiating hepatocyte injury in MASH are not yet definitively identified, but several candidates have been proposed. These include dysregulated circulating adipokines and inflammatory molecules [26][27][28][29], elevated circulating insulin and insulin like growth factor (IGF), and signals from the gut microbiome, which exhibits abnormalities in MASH patients and animal models. With the advent of single cell RNA sequencing technologies, subsets of hepatocytes have been identified that may selectively promote the development of MASLD [30].…”
Section: Upstream Drivers Of Hepatocyte Injury In Mashmentioning
confidence: 99%
“…Activated hepatic stellate cells (aHSCs) are a key cell-type that drives fibrogenesis in all forms of chronic liver disease, including NAFLD ( 9 ). HSCs comprise approximately 5-10% of the non-parenchymal cell population in the liver ( 10 ).…”
Section: Introductionmentioning
confidence: 99%